“Just Became a Love Slave”: Shedding Light on Relationship Violence Against Males - Albertus Christian; Khanis Suvianita (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2019)
“Violence”, in general, is a word associated with conduct more often perpetrated by males, whether against females or other males. Indeed, even in the field of ‘dating’, discussions on violence often deal specifically with it being against women, so that the term, “violence against women” has arisen. However, certain data indicates that this discussion should also involve violence against men. This discourse had apparently not yet surfaced, so the authors were interested in examining and seeking out what were male concepts, regarding any violence they may have experienced whilst in relationships. The results emerging indicated the existence of a number of concepts on particular facets of masculinity, those being of masculinity of either a romantic or a hegemonic nature. Overall, the situation puts males in the position of being the subject of high expectations of power, making the behavior of their partners to be considered as being non-violence. The overall organization of the discourse emerged in various forms, however these were of the same type as the discussion which has emerged concerning violence against women, so that it may be concluded that both of these topics are of similar importance, when it comes to their discussion.